Perspektif Gender dalam Tafsir Muhammad âAbduh - Samsukadi, Muchamad (Koordinatorat Perguruan Tinggi Agama Islam Swasta Wilayah IV Surabaya, 2014)
This article explains what Muhammad âAbduhâs interpretation on gender verses. According to âAbduh, Quran has broadly given same roles, duties and rights between men and women. However, sometimes the equal understanding has been forgotten by some mufasirs about verses dealing with leadership in household, polygamy, and inheritance. To âAbduh, in household, the relationship between husband and wife is mutualism-symbiosis. Functionally and structurally, it is lead by husband. Meanwhile, polygamy and inheritance are kinds of protection toward womenâs rights. Polygamy is forbidden to whom that has no ability to be fair, while inheritance has to be given equally and reasonably.